Determinants of cash waqf intention on female Muslim at Brunei and Indonesia - Susilo, Adib; Abdullah, Nurdianawati Irwani; Che Embi, Nor Azizan (USIM Press (Penerbit USIM), 2025)
This study's focus on investigating the determinants of cash waqf intention among female Muslims in Brunei and Indonesia for the purpose of comparing awareness about cash waqf between the two countries. By examining the factors influencing cash waqf intention in these two countries, the study not only shedding light on the attitudes and behaviours of female Muslims towards charitable giving but also providing insights into potential differences in awareness and participation levels between Brunei and Indonesia. Through purposive random sampling method, the study deploying 62 items of questionnaire to 106 Indonesian Muslim females and 105 Bruneian Muslim females. Integrating Theory of Planned Behaviour (TPB) determinants such as attitude, subjective norms, and perceived behavioural control with additional factors like literacy, religiosity, and trust enriches the analytical framework of this study. The multiple regression analysis allows this study to have a rigorous examination of the relationships between various factors and cash waqf intention among female Muslims in Brunei and Indonesia. The finding for both countries shows that religiosity and trust have no significant relationship with Muslim female intention to perform cash waqf. The findings shows that attitude, subjective norms, and perceived behavioural control have significant relationship in investigating female Muslim intention to perform cash waqf in Indonesia and Brunei Darussalam.